2015
DOI: 10.1002/2015gl065095
|View full text |Cite
|
Sign up to set email alerts
|

The Madden‐Julian Oscillation in a warmer world

Abstract: Global warming's impact on the Madden‐Julian Oscillation (MJO) is assessed using one of the few models capable in reproducing its key features. In a warmer climate predicted for the end of the century, the MJO increases in amplitude (by ~30%) and frequency, showing a more circumglobal propagation tendency. The MJO spatial extent becomes enhanced, deeper, and more zonally extended but meridionally confined. A stronger vertical tilting structure in diabatic heating, moisture, and convergence fields is seen. Our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
52
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(65 citation statements)
references
References 36 publications
11
52
2
Order By: Relevance
“…A similar result was found in the Goddard Institute for Space Studies model (Adames et al, ). Chang et al () analyzed historical and Representative Concentration Pathway 8.5 (RCP8.5) simulations of the ECHAM5‐SIT model and showed that the amplitude of MJO precipitation variability increases by about 17% in the future while zonal wind variability changes insignificantly. The studies above were conducted with a limited set of models, and there has not yet been a detailed mechanistic study using a multimodel data set to investigate the covariability in global warming‐induced MJO precipitation and wind variance changes.…”
Section: Introductionmentioning
confidence: 99%
“…A similar result was found in the Goddard Institute for Space Studies model (Adames et al, ). Chang et al () analyzed historical and Representative Concentration Pathway 8.5 (RCP8.5) simulations of the ECHAM5‐SIT model and showed that the amplitude of MJO precipitation variability increases by about 17% in the future while zonal wind variability changes insignificantly. The studies above were conducted with a limited set of models, and there has not yet been a detailed mechanistic study using a multimodel data set to investigate the covariability in global warming‐induced MJO precipitation and wind variance changes.…”
Section: Introductionmentioning
confidence: 99%
“…Both observational (Lee & Seo, 2011;Slingo et al, 1999) and modelling studies (e.g., Adames et al, 2017;Arnold et al, 2015;Chang et al, 2015;Liu et al, 2013;Maloney et al, 2019) suggest that the MJO precipitation variations tend to enhance in a warming climate, along with weak increase or even decrease of MJO wind variability and teleconnections due to increase of tropical static stability (Bui & Maloney, 2018;Maloney et al, 2019;Wolding et al, 2017). Both observational (Lee & Seo, 2011;Slingo et al, 1999) and modelling studies (e.g., Adames et al, 2017;Arnold et al, 2015;Chang et al, 2015;Liu et al, 2013;Maloney et al, 2019) suggest that the MJO precipitation variations tend to enhance in a warming climate, along with weak increase or even decrease of MJO wind variability and teleconnections due to increase of tropical static stability (Bui & Maloney, 2018;Maloney et al, 2019;Wolding et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…GCMs with various degrees of MJO simulation fidelity have been used to examine the response of the MJO to warming. While an accurate simulation of the MJO is a challenging task for many contemporary GCMs (Ahn et al, ; Jiang et al, ), many of these modeling studies have suggested an amplification of MJO variability and an increase in the frequency of the MJO in a warmer climate (Arnold et al, ; Carlson & Caballero, ; Chang et al, ; Liu, ; Liu et al, ; Song & Seo, ; Subramanian et al, ; Pritchard & Yang, ). With an atmosphere‐only GCM, Arnold et al () found MJO variability more than tripled as a response to an imposed 9°C SST increase.…”
Section: Introductionmentioning
confidence: 99%
“…With an atmosphere‐only GCM, Arnold et al () found MJO variability more than tripled as a response to an imposed 9°C SST increase. Using a coupled GCM, Chang et al () found that the period of the MJO changes from ∼50 days in a 20th century simulation to ∼30 days in a 21st.…”
Section: Introductionmentioning
confidence: 99%